Análisis comparativo de los ingresos y gastos de la Municipalidad Distrital de Emilio San Martín - Tamanco periodo 2016 - 2020 - Parimango Alvarez, Dennis Robert (2022)
The District Municipality of Emilio San Martín - Tamanco receives resources through different sources to finance expenses, which are usually insufficient. This doctoral thesis seeks to carry out a comparative analysis of the income and expenses of the District Municipality of Emilio San Martín - Tamanco in the period 2016 - 2020. With this objective, the present Quantitative type research was carried out, analytical level - Descriptive and non-experimental design. The investigation concludes that the budgetary execution of the municipality is 83.34%, since the income amounted to S/. 31,242,446.36 and expenses to S/. 26,037,603.48. Likewise, the most significant source of income was the Municipal Compensation Fund – FONCOMUN, having generated resources for S/. 10,897,080.65 equivalent to 34.88% of total income. The second largest source was Resources for Credit Operations, having obtained resources for S/. 10,642,601.94 meaning 34.06% of the total, thanks to loans obtained. The expenses of the institution amounted to the sum of S/. 26,037,603.48; explained mainly by the Goods and Services concept that reached the amount of S/. 9,470,054.88; which represents 36.37% of the total execution. The income and expenses of the entity had a decreasing behavior throughout the five years, being -8.05% for income and -0.24% for expenses.